Enhancing Graduate Competencies toImprove Industry Employability throughPre-Internship Training and Industrial Internship Programs - Sahid Triambudhi; Rosena Shintabella; Meyer Mega Eklesia Silaban (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
This community service project aims to strengthen student competencies through the implementation of both pre-internship briefing sessions and industrial internship placement. The program was carried out by the Department of Informatics Engineering at the Indramayu State Polytechnic (Polindra) as part of its commitment to improving students’ job readiness and aligning vocational education with industrial demands. The activity involved a structured workflow including industry needs identification, coordination with the Industrial Internship Program Team (PMI), preparation of learning materials, arrangement of seminar logistics, on-site briefing seminars, and post-program evaluations. A total of 182 students were successfully placed in various partner industries for internship programs following the briefing seminar. The results show significant improvements in students’ soft and technical skills, confidence levels, workplace adaptability, and understanding of professional ethics. Partner industries also provided positive feedback regarding student performance and contribution. The program demonstrated the essential role of vocational institutions in bridging academic knowledge and industrial application, while offering measurable benefits to both students and industry partners.